Natural Material-Based Art Learning Model Increases Aesthetic Experiences in Early Childhood - Fajrie, Nur; Kartika, Deny Dwi; Utaminingsih, Sri; Santoso, Deni Agung (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
The current problem is that people's understanding of art, especially regarding education, still needs to be improved. Teachers must still improve children's aesthetic experiences through nature-based learning and activities. This research aims to analyze art learning models based on natural materials to improve early childhood aesthetic experiences. The research approach used is quantitative, testing effectiveness using quick experiments and a non-equivalent control group design. The population in this study were students from 3 (three) kindergartens, totaling 33 children. The research sample in this study consisted of 33 children. The methods used to collect data are observation, interviews, and tests. Data were analyzed using normality and homogeneity tests. The t-test is also used to analyze learning effectiveness. The data analysis results show a significant difference between the pre-test and post-test in experimental groups 1 and 2. The difference between pre-test and post-test in the control group must be more significant (within the 95% confidence level). There is a difference in the average aesthetic experience of young children who were given action before and after using art learning based on natural materials. It was concluded that the application of an art learning model based on natural materials was effective in increasing aesthetic experiences in young children. The research implications can provide a theory of early childhood creativity in cognitive, affective and psychomotor development.